Ethnobotanical Study in Martinique of the Species Behind the Local Plant Name Bwa Kaka - Elodie Drane; Marie Feliot-Rippeault; Juliette Smith-Ravin; Odile François-Haugrin (Ethnobiology Letters, 2018)
Several scientific studies have reported that the sustainability of Traditional Knowledge (TK) is threatened by modernization. Plants of local pharmacopeias at the forefront of this phenomenon are those that are more discreet. Based on these observations, we focused on the case of a vernacular name attributed to a medicinal plant in Martinique: bwa kaka. It is reported in the literature as being highly sought after by the local population but there is a lack of information about plant species behind the denomination. To identify species that correspond to bwa kaka and to record the uses associated with them, a literature review of authors in the creolophone regions from the seventeenth century to the present day was performed, followed by an ethnobotanical survey among 80 people. A use value (UV) index was calculated. It was also determined whether there was convergence of uses between these different species. Additionally, this article examines the sociocultural (age, sex, residence) factors that could influence the answers. We found that ten species were called bwa kaka. Solanum triste was the most cited species, followed by Petiveria alliacea. Among these two, P. alliacea had the most cultural significance based on the calculated UV. Designated uses for each species were not significantly distinct according to Fisher’s Exact Test but they were significantly different depending on the sex of the interviewee. The number of uses cited was not correlated with the age of the interviewee.